Decision-making method for evaluating solar desalination options: the case of Saudi Arabia. Issue 3 (4th September 2019) - Shannak, Sa'd; Alnory, Malak
Abstract : Purpose: Solar as an energy source has a massive potential to reduce dependence on fossil fuels in Gulf Countries (GC). One attractive application of solar energy is solar-powered desalination, which is a viable method to produce fresh water. The most significant factor determining the potential deployment of this application is economics. Design/methodology/approach: In this study, the classical economic analysis model has been modified to assess the penetration of solar technology to power desalination plants at different periods during the project lifetime. Furthermore, the environmental and financial values were combined to assess the incentive of powering desalination plants with solar energy in Saudi Arabia. Three systems of solar technologies accompanied with water desalination based on technical applicability were modeled and economically analyzed to understand the impact of various design and operation parameters. Findings: This study shows that PV-RO is currently more competitive at both market and administrated prices in Saudi Arabia, followed by the MED-CSP system and finally CSP-RO system. CSP-RO system starts to generate positive surplus after 11 years, while the base case shows no positive surplus at all during the entire lifetime. Moreover, the same trend continues to hold with MED-CSP and PV-RO systems. The MED-CSP generates positive surplus after six years and PV-RO after five years only. On average, it takes eight years for a project running based on solar (CAPEX and OPEX) and desalination OPEX to generate positive cash surplus. Originality/value: This paper discusses the debate about incentives for renewable energy in GC and the impact of coupling water production and solar generation. Given that there is no analytical framework built earlier, this paper provides an alternative methodology for policy analysis to understand the role of economies of scope to incentivize solar generation. In other words, the authors are investigating options to reduce the total cost of solar production as a result of increasing the number of different goods produced.